2018
DOI: 10.20965/jdr.2018.p0453
|View full text |Cite
|
Sign up to set email alerts
|

Role of Real-Time GNSS in Near-Field Tsunami Forecasting

Abstract: This short paper reviews the role of real-time global navigation satellite system (GNSS) in near-field tsunami forecasting. Recent efforts highlight that coseismic fault model estimation based on real-time GNSS has contributed substantially to our understanding of large magnitude earthquakes and their fault expansions. We briefly introduce the history of use of real-time GNSS processing in the rapid estimation of the coseismic finite fault model. Additionally, we discuss our recent trials on the estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Furthermore, TVA represents a low-cost tool, ready to be implemented on existing high-rate GNSS real-time networks and to push forward the installation of new dense GNSS real-time networks. Finally, TVA main goal is to represent an additional resource to classic methods, such as tsunami forecast 62 , earthquake early warning for tsunami alert 63 , tsunami inundation simulation and damage estimation 64,65 ; in this context, the synergic use of all the available tools could really enhance the already existing tsunami warning systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TVA represents a low-cost tool, ready to be implemented on existing high-rate GNSS real-time networks and to push forward the installation of new dense GNSS real-time networks. Finally, TVA main goal is to represent an additional resource to classic methods, such as tsunami forecast 62 , earthquake early warning for tsunami alert 63 , tsunami inundation simulation and damage estimation 64,65 ; in this context, the synergic use of all the available tools could really enhance the already existing tsunami warning systems.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we show that equally good forecasts can be made using only a few minutes of data from an existing network of Global Navigation Satellite System (GNSS) stations. Tsunami warning centers are already starting to incorporate this data in performing earthquake magnitude estimates, and it has been shown that the use of GNSS data can have great benefits, particularly for near-field forecasting (Crowell et al, 2018;Ohno et al, 2022;Ohta et al, 2018;Williamson et al, 2020). We show that this can be taken further by training Convolutional Neural Networks (CNNs) to forecast the tsunami waveforms directly from the GNSS waveforms.…”
Section: Introductionmentioning
confidence: 97%
“…The finite fault models estimated by REGARD are helpful for obtaining the initial sea surface distribution for tsunami forecasting. The consortium led by Tohoku University has developed a real-time damage estimation system for tsunami inundation using the REGARD fault model as an initial tsunami source model (Musa et al 2018;Ohta et al 2018). This system is expected to be used for the initial response of the government when a disaster occurs.…”
Section: Introductionmentioning
confidence: 99%